Measurement of the jet mass in highly boosted ${t}\overline{t}$ events from pp collisions at $\sqrt{s}=8$ $\,\text {TeV}$ - CMS collaboration (2230 authors) (2017)
The first measurement of the jet mass $m_{\text {jet}}$ of top quark jets produced in ${t}\overline{t} $ events from pp collisions at $\sqrt{s}=8$ $\,\text {TeV}$ is reported for the jet with the largest transverse momentum $p_{T}$ in highly boosted hadronic top quark decays. The data sample, collected with the CMS detector, corresponds to an integrated luminosity of 19.7 $\,\text {fb}^{-1}$ . The measurement is performed in the lepton+jets channel in which the products of the semileptonic decay ${t} → b W$ with $W→ \ell ν $ where $\ell $ is an electron or muon, are used to select ${t}\overline{t} $ events with large Lorentz boosts. The products of the fully hadronic decay ${t} → b W$ with $W→ q \overline{q} '$ are reconstructed using a single Cambridge–Aachen jet with distance parameter $R=1.2$ , and $p_{T} >400$ $\,\text {GeV}$ . The ${t}\overline{t} $ cross section as a function of $m_{\text {jet}}$ is unfolded at the particle level and is used to test the modelling of highly boosted top quark production. The peak position of the $m_{\text {jet}}$ distribution is sensitive to the top quark mass $m_{{t}}$ , and the data are used to extract a value of $m_{{t}}$ to assess this sensitivity.